Initiation of female cones of Pinus cembroides Zucc. - Zavala Chávez, Fernando; García Moya, Edmundo (Instituto de Ecología, A.C., 1990)
The development of Winter apical buds and the initiation of female cones of Pinus cembroides in the Southern Sierras of the State of San Luis Potosí, were studied during 1985 and 1986. The initiation of cone primordia was delayed in 1985 approximately one month in comparison with 1986. This phenomenon coincided with differences of precipitation and temperature in relation to the 11 years average of the nearest climatological station (El Peaje). The course of precipitation and temperature for 1986 resembled the average and hence can be considered as more representative for the area; in that year the initiation of cone primordia ranged from middle August to late September (or early October). Annual fluctuation of precipitation and temperature may cause changes in the period of differentiation of cone primordia.